Transformational Science and Technology for the Current and Future Force 2006
DOI: 10.1142/9789812772572_0023
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Water Detection by Fusing Multiple Cues for Autonomous Off-Road Navigation

Abstract: Detecting water hazards is a significant challenge to unmanned ground vehicle autonomous off-road navigation. This paper focuses on detecting the presence of water during the daytime using color cameras. A multi-cue approach is taken. Evidence of the presence of water is generated from color, texture, and the detection of reflections in stereo range data. A rule base for fusing water cues was developed by evaluating detection results from an extensive archive of data collection imagery containing water. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 2 publications
0
34
0
11
Order By: Relevance
“…The work in [7], [8], [9] uses conventional visible passive imagery to detect bodies of water. In [7] and [8] the authors detect water by fusing multiple cues like color, brightness and stereo depth to train a classifier.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The work in [7], [8], [9] uses conventional visible passive imagery to detect bodies of water. In [7] and [8] the authors detect water by fusing multiple cues like color, brightness and stereo depth to train a classifier.…”
Section: Related Workmentioning
confidence: 99%
“…In [7] and [8] the authors detect water by fusing multiple cues like color, brightness and stereo depth to train a classifier. The recent work in [9] is for monocular vision and looks to generate a physical model of bodies of water lying on or nearby roads.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, it has been shown that the unitary-category classification of Bao 35 demonstrates a better performance compared to another state-of-the-art approach. 46 We have extended the unitary-category classification of Bao et al 35 into multicategory classification and applied contextual information as a special feature. With our contribution, we have shown that our gravity model for region labeling outperforms the results achieved by Bao et al We have evaluated the performance of our gravity model on the WATERVisie dataset.…”
Section: Object-centric Region Labelingmentioning
confidence: 99%
“…The detection of puddles and other water hazards allows the usage of several sensor systems. The camera-based water detection presented in [17] uses color, texture and stereo range data. A polarization-based approach is described in [20].…”
Section: Negative Obstacles Water and Groundmentioning
confidence: 99%